Kesesuaian Aseptik Dispensing Injeksi Antibiotik Pada Pasien Anak Rumah Sakit Umum Daerah dr. Soediran Mangun Sumarso Wonogiri - eny rusmiyati (Jurnal Farmasi (Journal of Pharmacy), 2022)
The use of injection preparations in hospitalized patients has a high prevalence rate so that dispensing injections needs attention because there are many risks that can arise during the mixing process. The purpose of the study was to determine the suitability of the aseptic procedure for dispensing antibiotics in pediatric patients with standard operating procedures applicable at the dr. Sudirman Mangun Sumarso Wonogiri. This study used a retrospective method with descriptive analysis of the data for August – October 2021. Conformity was measured using a checklist form and the percentage of conformity was calculated. The results showed that from 106 antibiotic mixtures consisting of Cefotaxim inj (46%), Ceftriaxon inj (12%), Chloramphenicol inj (3%), and Gentamicin inj (39%) obtained 85.71% according to standard operating procedures. Compliance that has met the standard includes reviewing prescriptions, doing 5 correct, calculating dosage suitability, choosing solvents, calculating solvent volumes, making delivery forms and those that are not appropriate, namely checking the condition of the drug when it is received. Examination of the condition of the drug when it is received should be carried out accompanied by a form so that there is a record that can be used for tracing when a medication error occurs.